2005
DOI: 10.1158/0008-5472.can-04-4575
|View full text |Cite
|
Sign up to set email alerts
|

A Hypoxia-Driven Vascular Endothelial Growth Factor/Flt1 Autocrine Loop Interacts with Hypoxia-Inducible Factor-1α through Mitogen-Activated Protein Kinase/Extracellular Signal-Regulated Kinase 1/2 Pathway in Neuroblastoma

Abstract: Flt1, an ''fms-like tyrosine kinase'' receptor, has been suggested to play an active role in vascular endothelial growth factor (VEGF)-mediated autocrine signaling of tumor growth and angiogenesis. Here, we used a neuroblastoma model to investigate the role of VEGF/Flt1 signaling in hypoxiamediated tumor cell survival, drug resistance, and in vivo angiogenesis. SK-N-BE(2), a highly malignant neuroblastoma cell line resistant to hypoxia-induced apoptosis expresses active Flt1 but lacks VEGFR2 expression. We fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 47 publications
(65 reference statements)
10
118
0
Order By: Relevance
“…In the tumor microenvironment, hypoxia can cause some effector cells to produce HIF-1␣, which is the upstream regulatory gene of VEGF (42). VEGF also has been demonstrated to interact with the HIF-1␣ via an autocrine loop (43,44). The level of VEGF and HIF-1␣ could directly and indirectly indicate the ability of a tumor to cause angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor microenvironment, hypoxia can cause some effector cells to produce HIF-1␣, which is the upstream regulatory gene of VEGF (42). VEGF also has been demonstrated to interact with the HIF-1␣ via an autocrine loop (43,44). The level of VEGF and HIF-1␣ could directly and indirectly indicate the ability of a tumor to cause angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of Flt1 in several tumor cells suggest that VEGF/Flt1 signaling has autocrine survival activity [15][16][17][18]. Treatment with anti-VEGF and anti-Flt1 antibodies inhibits ERK1/2 activation and downregulates Bcl-2 expression in the highly malignant neuroblastoma cell line SK-N-BE(2) [19]. Furthermore, reduced endogenous VEGF or VEGFR1 expressions induce apoptosis in MDA-MB-231 and MCF-7 breast cancer cells [20].…”
Section: Genes Regulated By Zfat In the Functions Of Apoptosis Cell mentioning
confidence: 99%
“…In particular, epidermal growth factor receptor (EGFR) modulates HIF-1a levels in prostate, lung and breast cancer cells (Zhong et al, 2000;Phillips et al, 2005;Peng et al, 2006). Studies in neuroblastoma cells have indicated the presence of a hypoxia-driven VEGF/ VEGFR-1 autocrine loop modulating HIF-1a (Das et al, 2005). Whether other RTKs are capable of modulating HIF-1a, and whether RTKs can modulate HIF-2a levels is unknown.…”
Section: Introductionmentioning
confidence: 99%